Representing and Visualizing in Landscape, between Hard Sciences and Humanities (diségno, 2019)
The issue proposed in the call ‘The representation oflandscape, territory and environ ment’ is placed in the crossing of various disciplines: geography, ecology, urban design, architecture, but also social sciences and humanities, till to include the latest interdisciplinary exchange between life sciences and techniques which is on the basis of computation. (read more)